Effects of Components on Qualities of Crispy Bamboo Shoot Snack - Charoenphun, Narin; Pakeechai, Kanokporn (Journal of Food Health and Bioenvironmental Science, 2023)
The objective of this research was to study the effect of ingredients on the quality of crispy bamboo shoot snack. The effects of different ratios of tapioca flour and bamboo shoots on the quality of crispy bamboo shoot snack were studied. It was found that the optimum ratio of tapioca flour and bamboo shoot was 50:50. It had good appearance and swelling rate after frying. Moreover, the aroma of bamboo shoots was clear. The effects of different flour types on the quality of crispy bamboo shoot snack were investigated. It was found that tapioca flour was suitable flour for crispy bamboo shoot snack production. It had good appearance and swelling rate after frying that it was higher than the formula using glutinous rice flour, rice flour and wheat flour. In addition, the texture of the crispy bamboo shoot snack was crispy at an appropriate level. The effects of flavoring with various flavors on the sensory acceptance of consumers were investigated. The original, seaweed mixed with black sesame and spicy flavors had a higher score in appearance, flavor, taste, texture and overall liking score than other flavors. The analysis of the chemical composition of crispy bamboo shoot snack was investigated. The moisture, protein, fat, total carbohydrate, ash, and energy were 2.73-3.50 %, 1.04-2.39 %, 26.91-28.53 %, 66.36- 66.67 %, 1.89-1.98 % and 513.08-523.81 kcal, respectively. It can be used as a guideline for crispy bamboo shoot snack production for commercial distribution.